Infra Red Aerial Photograph Interpretation for Soil Erosion at Wuryantoro, Wonogiri - S Suharjo; Sugiharto Budi Santoso; Pujo Nur Cahyo; M Mulyono; Heru Sri Widodo (Forum Geografi, 2001)
Collecting data of soil erosion hazard terrestrially needs much time, high cost, and large energy. Therefore it is needed appropriate technology in addition to terrestrially decreasing necessity of time, cost and energy. Aerial photograph is picture of earth surface, which shape and place similar to condition on earth surface. Using aerial photograph in this research is expected to be able to take account for erosion factors. This research is conducted in Kecamatan Wuryantoro Kabupaten Wonogiri. Research method that used is aerial photograph interpretation with land unit approach. Amounts of soil lost are approached with USLE formula. Aerial photograph that used in this research is aerial photograph coloured infrared with 1:10.000 in scale and 1991 in year of taking photography. The result shows that using aerial photograph is very useful in supporting soil erosion rate calculation. Erosion rate at research area is 0.0968 ton/ha/year to 100.4344 ton/ha/year. This number is included in class of light erosion hazard (